Refractive errors and their effects on visual evoked potentials - Ruchi Kothari; Pradeep Bokariya; Smita Singh; Purvasha Narang; Ramji Singh (Journal of Clinical Ophthalmology and Research, 2014)
In view of the increasing use of visual evoked potentials (VEP) technique in neuro-ophthalmological diagnosis, it was thought pertinent to appraise the changes brought about in VEPs in the presence of refractive error (RE) as studied by the vision researchers and neurophysiologists. The purpose of this review was to provide a comprehensive quintessence of the work carried out in this fi eld with an attempt to summarize the previous concepts, recent perspective and current notion about the value of RE in electrophysiologic testing particularly the VEP technique.